Dijitalisasyon ng diksyunaryong pangmatematika: Pagpapalakas sa wika sa pamamagitan ng sumisibol na teknolohiya - Garcia, Lakangiting Caparanga (Animo Repository, 2001)
Proving the ability of the Filipino language to adjust to technological developments is the main reason behind the creation of this dissertation. The book by Dr. Maxima Acelajado and Lakangiting Garcia entitled Terminolohiyang Pangmatematika was used as springboard in making the digital dictionary. Entries in the dictionary was classified as 'labi', 'umiiral' and 'sumisibol' based on the theory of Raymond Williams. Such classification was made to give the users of the digital dictionary information regarding the state of each entry.After developing the digital dictionary, respondents were selected to evaluate it. Totalling 45, respondents were composed of 15 teachers (5 elementary, 5 high school and, 5 college) and 30 college students (15 public and 15 private). After evaluation, results were interpreted by computing for the overall mean of the assessment results.The tabulated results proved that the classification made for each word entry is correct and effective and the digital dictionary produced is an exceptional aid in both teaching and studying.